2011
DOI: 10.1017/s0967199410000638
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes of sheep cumulus–oocyte complexes following different methods of vitrification

Abstract: To determine the ultrastructural changes of sheep cumulus-oocyte complexes (COCs) following different methods of vitrification, good quality isolated COCs (GV stage) were randomly divided into the non-vitrified control, conventional straw, cryotop and solid surface vitrification groups. In both conventional and cryotop methods, vitrified COCs were respectively loaded by conventional straws and cryotops, and then plunged directly into liquid nitrogen (LN2); whereas in the solid surface group, vitrified COCs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
2
7
1
Order By: Relevance
“…Concerning the morphology of other organelles, our data are generally in agreement with previous studies on ovine oocyte ultrastructure. In fact, the morphology of mitochondria, lipid droplets, Golgi complexes and endoplasmic reticulum, before and after maturation, were comparable with previous reports on prepubertal and adult sheep oocytes matured in vitro [ 16 , 17 , 22 ] or in vivo [ 27 29 ]. As well, we observed that the organelle redistribution during maturation was coincident with what described by others, both in vitro and in vivo [ 16 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the morphology of other organelles, our data are generally in agreement with previous studies on ovine oocyte ultrastructure. In fact, the morphology of mitochondria, lipid droplets, Golgi complexes and endoplasmic reticulum, before and after maturation, were comparable with previous reports on prepubertal and adult sheep oocytes matured in vitro [ 16 , 17 , 22 ] or in vivo [ 27 29 ]. As well, we observed that the organelle redistribution during maturation was coincident with what described by others, both in vitro and in vivo [ 16 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Deleterious effects of vitrification, such as retraction of cumulus cell projections, were observed in vitrified sheep COCs [79], similar to immature vitrified COCs from primed rats, were a reduction of F-actin in ooplasm and oocyte cortex was associated to irreversible but irregular retraction of transzonal projections [35]. The mechanical removal of cumulus cells from immature bovine oocytes did not affect their maturation competence but reduced blastocyst rates, when compared with intact COCs [80].…”
Section: Somatic Compartments In Ivm and Vitrificationmentioning
confidence: 99%
“…Higher degrees of mitochondrial swelling were observed in previous studies on cryopreserved grade I and II sheep embryos [2,5]. Mitochondrial swelling is also commonly described in cryopreserved oocytes [14,16,23]. Using in vitro produced embryos and similar procedures of slow freezing and vitrification Bettencourt et al [3] achieved satisfactory pregnancy rates of 68.4% and 54.6% on day 45, respectively.…”
Section: Discussionmentioning
confidence: 79%